2020
DOI: 10.26803/ijlter.19.7.12
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Higher-Order Thinking Skills among Home Science Students: The Effect of Cooperative Learning Student Teams- Achievement Divisions (STAD) Module

Abstract: This study aims to investigate the effectiveness of the cooperative learning module using Student Teams-Achievement Divisions (STAD) techniques in enhancing students' HOTS achievement in the topic of the digestive system and food absorption. A quasi-experimental design was used in this study to gauge the effectiveness of the module. Purposive sampling technique was used to choose the respondents. The study involved 182 students who represented the experimental group and the conventional group. Students were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…In line with previous research that state STAD is the simplest cooperative learning model so it is widely used in cooperative learning and emphasizes the Student process Team Learning (Syakur et al, 2020;Yulianto et al, 2020). Than the use of stad also supported by the other researcher that state, one of the advantages of the STAD learning model is that each group consists of heterogeneous students (Silalahi et al, 2021;Takko et al, 2020). By forming heterogeneous groups, students are expected to more easily master learning materials through small group discussions and collaborations consisting of 4 to 5 people.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In line with previous research that state STAD is the simplest cooperative learning model so it is widely used in cooperative learning and emphasizes the Student process Team Learning (Syakur et al, 2020;Yulianto et al, 2020). Than the use of stad also supported by the other researcher that state, one of the advantages of the STAD learning model is that each group consists of heterogeneous students (Silalahi et al, 2021;Takko et al, 2020). By forming heterogeneous groups, students are expected to more easily master learning materials through small group discussions and collaborations consisting of 4 to 5 people.…”
Section: Discussionsupporting
confidence: 63%
“…One of the advantages of the STAD learning model is that each group consists of heterogeneous students. By forming heterogeneous groups, students are expected to more easily master learning materials through small group discussions and collaborations consisting of 4 to 5 people (Takko et al, 2020). In addition, previous study also found that STAD can meet the needs of students in critical thinking, problem solving together and integrating knowledge and experience (Silalahi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students need to be taught critical thinking and higher-order thinking abilities to achieve this learning activity (Anisa, 2017;Hidayatullah et al, 2021;Pursitasari et al, 2020). HOTS are a higher level of thinking created by pupils via the use of numerous concepts and methodologies (Arifin & Retnawati, 2017;Takko et al, 2020). Bloom's Taxonomy-based thinking model includes HOTS as well.…”
Section: Introductionmentioning
confidence: 99%
“…The LOTS stage only explores students' abilities to remember, understand, and apply concepts. These are less relevant to apply to the 21stcentury learning system (Takko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%